On Distribution of Superconductivity in Metal Hydrides - Semenok, Dmitrii V.; Kruglov, Ivan A.; Savkin, Igor A.; Kvashnin, Alexander G.; Oganov, Artem R. (Current opinion in solid state & materials science, 2020)
•Highest-TC hydrides are formed by metals in the “lability belt” of the Periodic Table, roughly between 2 and 3 groups.•~0.3 electrons should be transferred to H-atom in XH10±2 hydrides to make it the most effective superconductors.•TC decreases with increasing number of d- and f-electrons and fully disappears when magnetic order sets in. Using the data on the superconducting critical temperature (TC) for a number of metal hydrides, we found a rule that makes it possible to predict the maximum TC based only on the information about the electronic structure of metal atoms. Using this guiding principle, we explored the hydride systems for which no reliable information existed, predicted new higher hydrides in the K-H, Zr-H, Hf-H, Ti-H, Mg-H, Sr-H, Ba-H, Cs-H, and Rb-H systems at high pressures, and calculated their TC. The highest-temperature superconducting hydrides are formed by metals in the “lability belt” roughly between 2nd and 3rd groups of the Periodic Table. Results of the study of actinoids and lanthanoids show that they form highly symmetric superhydrides XH7-XH9, but the increasing number of d- and especially f-electrons affects superconducitivity adversely. Hydrides of late transition metals (e.g. platinoids) and all but early lanthanoids and actinoids are not promising for high-Tc superconductivity. Designed neural network allowing the prediction of TC of various hydrides shows high accuracy and was used to estimate upper limit for TC of hydrides for which no date are avilable. The developed rule, based on regular behavior of the maximum achievable critical temperature as a function of number of d + f electrons, enables targeted predictions about the existence of new high-TC superconductors.